Meningkatkan Kemampuan Menggosok Gigi Menggunakan Game Menggosok Gigi Pada Siswa Tunagrahita Ringan - Winda Wahyuni; Jon Efendi (Jurnal Penelitian Pendidikan Khusus, 2022)
This study focused on improving the ability to brush teeth using a tooth brushing game. This study aims to find out how the process of brushing teeth by using a game of brushing teeth for students with light impairment. This research use a form of qualitative approach with this type of class action research is a research method that will be used. The subject of this study is aimed at self-building learning brushing teeth. The data analysis techniques used in this study are collecting data, reducing data and drawing conclusions. Research is carried out as many as two cycle, each cycle begins with planning, action, observation and reflection. The results obtained in the first cycle of each learner experienced an increase but only one student research the KKM limit while in the cycle two learners had increased and obtained the value of reaching the KKM limit. Conclusion of ability to brush teeth experienced a significant increase using the game of brushing teeth.